Technology transfers, foreign investment and productivity spillovers - Newman, Carol (My University, 2015)
This paper explores the relationship between foreign direct investment (FDI) and the productivity of host country domestic firms. We rely on a specially designed survey of over 4000 manufacturing firms in Vietnam, and separate out productivity gains along the supply chain (obtained through direct transfers of knowledge/technology between linked firms) from productivity effects through indirect FDI spillovers. In addition to identifying indirect vertical productivity spillovers from FDI, our results show that there are productivity gains associated with direct linkages between foreign-owned and domestic firms along the supply chain not captured by commonly used measures of spillovers. This includes evidence of productivity gains through forward linkages for domestic firms which receive inputs from foreign-owned firms.
PUBLISHED
Keywords: Foreign direct investment; Productivity spillovers; Direct linkages; Technology transfers; Vietnam; International Development; International Integration; Development economics; International economics, finance, trade and development